The Problem of Artistic - Psychological Image in Boburnoma (Eurasian Scientific Herald, 2022)
In addition to being a historical literary memoir, Boburnoma is also an autobiographical work. At the center of the events of the work is the personality of Babur. The successful expression of the text of "Boburnoma" is also distinguished by the fact that it depicts a number of psychic lines. This article deals with the problem of artistic and psychological image in "Boburnoma"